2023
DOI: 10.3390/toxics11070569
|View full text |Cite
|
Sign up to set email alerts
|

Benchmark Dose Approach to DNA and Liver Damage by Chlorpyrifos and Imidacloprid in Male Rats: The Protective Effect of a Clove-Oil-Based Nanoemulsion Loaded with Pomegranate Peel Extract

Abstract: Pesticides are widely used around the world to increase crop production. They also have negative impacts on animals, humans, and the ecosystem. This is the first report evaluating a novel pomegranate-extract-loaded clove-oil-based nanoemulsion (PELCN) and its potential for reducing oxidative stress and DNA damage, as well as its hepatoprotective effects against imidacloprid (IM) and chlorpyrifos (CPF) toxicity in male rats. The benchmark dose (BMD) approach was also used to study the dose–response toxicity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 128 publications
1
0
0
Order By: Relevance
“…Furthermore, a signi cant upsurge was observed in the AST activity in the IM, IM + AR100 and IM + AR200 groups relative to the DW group, respectively, in the present study. In agreement with our ndings in the current study, other researchers have reported signi cant elevations in the levels of ALT and AST in rats (Askri et al 2022, Omar et al 2023. Increased levels of ALT and AST have been associated with hepatic damage as a result of heightened cell membrane absorptivity (Toghan et al 2022).…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, a signi cant upsurge was observed in the AST activity in the IM, IM + AR100 and IM + AR200 groups relative to the DW group, respectively, in the present study. In agreement with our ndings in the current study, other researchers have reported signi cant elevations in the levels of ALT and AST in rats (Askri et al 2022, Omar et al 2023. Increased levels of ALT and AST have been associated with hepatic damage as a result of heightened cell membrane absorptivity (Toghan et al 2022).…”
Section: Discussionsupporting
confidence: 93%